Aktivitas Antibakteri Senyawa Turunan Oleanan dari Kayu Akar Pterospermum Subpeltatum - Salempa, Pince; Noor, Alfian; Hariani, Nunuk; Harlim, Tjodi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
A triterpenoid derivative compound, oleane-12-en-2,3,23-triol-28-oat, from chloroform fraction of root wood ofPterospermum subpeltatum C. B. Rob (Sterculiaceae) was identified using IR, 1H dan 13C NMR data. The compoundhas shown toxicity against Artemia salina, LC50 of 46.06 μg/mL, and antibacterial potential upon Shigella boydii andStaphylococcus aureus with inhibition zones of 8.3 and 9.8 mm respectively.